2020
DOI: 10.1002/jbmr.4637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HMGB1/RAGE Signaling Reduces the Incidence of Medication-Related Osteonecrosis of the Jaw (MRONJ) in Mice

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication of antiresorptive or antiangiogenic medications, used in the treatment of bone malignancy or osteoporosis. Bone necrosis, mainly represented by osteocytic death, is always present in MRONJ sites; however, the role of osteocyte death in MRONJ pathogenesis is unknown. High mobility group box 1 (HMGB1) is a non-histone nucleoprotein that in its acetylated form accumulates in the cytoplasm, whereas non-acetylated HMGB1 localizes in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Osteocytic death during MRONJ likely involves multiple mechanisms, including apoptosis and cell necrosis, and is observed at early stages of disease setting. ( 97 , 98 , 99 ) Dying osteocytes release cellular signals that enhance the degree and severity of periodontal tissue inflammation. The presence of necrotic bone that cannot be removed further inhibits healing of periodontal tissues.…”
Section: Proposed Clinical Model Of Mronj Pathophy...mentioning
confidence: 99%
“…Osteocytic death during MRONJ likely involves multiple mechanisms, including apoptosis and cell necrosis, and is observed at early stages of disease setting. ( 97 , 98 , 99 ) Dying osteocytes release cellular signals that enhance the degree and severity of periodontal tissue inflammation. The presence of necrotic bone that cannot be removed further inhibits healing of periodontal tissues.…”
Section: Proposed Clinical Model Of Mronj Pathophy...mentioning
confidence: 99%
“…It has been demonstrated that this lacunar–canalicular network acts as a mechano-sensing system [ 10 , 11 , 12 ] that regulates bone remodeling not only by controlling osteoblast and osteoclast function but also by modulating the gradient of ionic substitutions in bone mineralization [ 13 , 14 , 15 ]. Importantly, previous studies have indicated the association of osteocyte death and empty osteocyte lacunae with impaired bone remodeling and jawbone necrosis in MRONJ [ 16 , 17 , 18 ]. However, the exact conditions and roles of osteocytes in MRONJ remain unclear.…”
Section: Introductionmentioning
confidence: 99%